Clinical review of the impacts of hepatitis C : short life working group report for the Scottish Government : informing decision making on awards for people, without advanced hepatitis C (HCV) disease, who were infected with hepatitis C through NHS blood transfusion/treatment with blood products, and for their widows, widowers, civil partners or long-term partners.: short life working group report for the Scottish Government : informing decision making on awards for people, without advanced hepatitis C (HCV) disease, who were infected with hepatitis C through NHS blood transfusion/treatment with blood products, and for their widows, widowers, civil partners or long-term partners. (2018) - Unknown
No abstract available